Aluminium phosphide-induced genetic and oxidative damages in vitro: Attenuation by Laurus nobilis L. leaf extract - Türkez, Hasan (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVE: The present investigation was undertaken to assess the protective effect of Laurus nobilis leaf extract (LNE) against aluminum phosphide (AIP)-induced genotoxic and oxidative damages stress in cultured human blood cells in the presence of a metabolic activator (S9 mix). MATERIALS AND METHODS: Sister chromatid exchange (SCE) and chromosome aberration (CA) assays were used to assess AlP-induced genotoxicity and to establish the protective effects of LNE. In addition, we determined total antioxidant capacity (TAC) and total oxidative status (TOS) levels in AlP and LNE treated cultures for biomonitoring the oxidative alterations. RESULTS: There was significant increases (P < 0.05) in both SCE and CA frequencies of cultures treated with AlP as compared to controls. Our results also showed that AlP (58 mg/l) caused oxidative stress by altering TAC and TOS levels. However, co-application of LNE (25, 50, 100 and 200 mg/l) and AlP resulted in decreases of SCE, CA rates and TOS level and increases of TAC level as compared to the group treated with AlP alone. CONCLUSION: The preventive role of LNE in alleviating AlP-induced DNA and oxidative damages was indicated for the first time in the present study.